HUMANISM PERSPECTIVE OF INDONESIAN POP MUSIC ALBUM COVERS IN THE 1980S ERA - Dewanto, Inko Sakti (Sanata Dharma University, 2025)
This study investigates the visual representation of Indonesian pop musicians on album covers from the 1980s and examines how these visual artifacts reflect and reinforce deeper humanistic values. During this period, pop culture in Indonesia experienced a significant transformation, with musicians gaining popularity through their music and the symbolic construction of their public image, especially via album covers. These covers functioned as powerful cultural texts, shaping public perception, constructing idealized identities, and influencing the emotional and aspirational relationships between idols and their fans. Employing a qualitative approach grounded in the humanism perspective, the study used five ontological elements of humanism—the self-interpreting animal, purposeful agent, language animal, dialoguing animal, and embodied subject—as analytical tools to unpack the visual strategies employed in these album covers. These elements helped explain how musicians were portrayed as entertainers and as representations of human ideals and existential values. The analysis reveals that album covers fostered a form of idolization that aligned with humanistic desires for identity, purpose, and self-fulfillment. These visual narratives supported the cult of personality and embedded ideological meanings that continue to resonate in contemporary pop culture. This research contributes to the broader discourse on design, cultural identity, and humanist thought in contemporary Indonesian visual culture.